EFEKTIVITAS PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DI SMP NEGERI 7 PADANGSIDIMPUAN - Melati Kartika Hutauruk; Yulia Pratiwi Siregar; Eva Yanti Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
Abstrak This study aims to describe of using realistic mathematical learning on students’ mathematical creative thinking ability on the topic solid figure at the eighth grade students of SMP Negeri 7 Padangsidimpuan. The research was conducted by applying experimental method (one group pretest post test design) with 25 students as the sample and they were taken by using simple random sampling technique from 153 students. Observation and test were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using realistic mathematical learning was 3.5 (very good category) and (b) the average of students’ solid figure achievement before using realistic mathematical learning was 61.64 (enough category ) and after using realistic mathematical learning was 78.92 (good category). Furthermore, based on inferential statistic by using pair sample ttest (SPSS 17), the result showed significant value was less than 0.05(0.00 < 0.05). It means realistic mathematical learning was effective used on students’ mathematical creative thinking ability on the topic solid figure at the eighth grade students of SMP Negeri 7 Padangsidimpuan. Keywords: Realistic Mathematical Learning, Mathematical Creative Thinking Ability